Resolved ALMA [C ii] 158 μm Observations at Cosmic Noon: Interstellar Medium Structure and Dynamics of the Starbursting QSO SDSS J1000 - Christopher Rooney; Bo Peng; Amit Vishwas; Gordon Stacey; Thomas Nikola; Cody Lamarche; Catie Ball; Carl Ferkinhoff; Drew Brisbin; Steven Hailey-Dunsheath (The Astrophysical Journal)
We present spatially resolved Atacama Large Millimeter/submillimeter Array Band 9 observations of the [C ii ] 158 μ m fine structure line from an optically selected quasar, SDSS J100038.01+020822.4 (J1 000 ), at z = 1.8275. By utilizing [O i ] 63 μ m line observations from Herschel/PACS and constructing a detailed dust spectral energy distribution using Herschel and Spitzer archival imaging data, we show that the [C ii ] line emission is well explained by a photodissociation region (PDR) model, in which the emission arises from the surfaces of molecular clouds exposed to far-UV radiation fields ∼5 × 10 ^3 times the local interstellar radiation field ( G _0 ). We find a factor of 30 variation in spatially resolved [C ii ]/far-IR continuum across the source, which is explained by the reduced fraction of cooling via [C ii ] line emission at such high far-UV field strengths. By matching the derived PDR parameters to the observed far-IR line and continuum intensities we derive cloud size scales and find that typical cloud radii in J1000 are ∼3.5 pc, perhaps indicating an interstellar medium that is highly fractured due to intense star formation activity. We model the galaxy dynamically and find that the [C ii ] emission is contained within a compact, dynamically cold disk with v / σ  = 6.2, consistent with the IllustrisTNG50 cosmological simulation. We also report the discovery of a companion galaxy to J1 000 confirmed by the detection of [C ii ] and use recently obtained JWST/NIRCam imaging of the system to argue for J1 000 being an interacting system. With total stellar mass ∼ 1.5 × 10 ^10 M _⊙ and main-component dynamical mass ≳ 10 ^11 M _⊙ , the J1 000 system is a progenitor to the most massive galaxies seen in the local Universe.